2013
DOI: 10.1186/1472-6963-13-176
|View full text |Cite
|
Sign up to set email alerts
|

Measuring fragmentation of ambulatory care in a tripartite healthcare system

Abstract: BackgroundHong Kong has a tripartite healthcare system, where western medicine provided in both public and private sectors coexist with Chinese medicine practice. The purpose of this study is to measure fragmentation of ambulatory care experienced by the non-institutionalized population aged 15 and over in such a tripartite system, thus shed light on the ongoing primary care reform.MethodsThis is a cross-sectional secondary data analysis using the Thematic Household Survey, which was conducted by the Hong Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Studies related to fragmentation of care delivery across multiple providers have shown that a mean FCI of 0.50 corresponds to moderate levels of care fragmentation and a mean FCI of 0.70 corresponds to moderately high levels of care fragmentation 20 22. While our study did not factor in care fragmentation associated with coordinating care across multiple healthcare entities and focused on multispecialty care fragmentation in a single institution, we found that moderately high (FCI ≥0.7) levels of care fragmentation persists in around 36% of the outpatient population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies related to fragmentation of care delivery across multiple providers have shown that a mean FCI of 0.50 corresponds to moderate levels of care fragmentation and a mean FCI of 0.70 corresponds to moderately high levels of care fragmentation 20 22. While our study did not factor in care fragmentation associated with coordinating care across multiple healthcare entities and focused on multispecialty care fragmentation in a single institution, we found that moderately high (FCI ≥0.7) levels of care fragmentation persists in around 36% of the outpatient population.…”
Section: Discussionmentioning
confidence: 99%
“…The Fragmentation of Care Index (FCI) was developed from the Continuity of Care Index,20 22 introduced by Bice and Boxerman 25 28. It is a measure of dispersion of the patient care based on the number of patient visits, number of different providers visited and number of visits to each provider.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients experience a fragmented healthcare journey that involves transitions of care between multiple primary, secondary and tertiary care settings 1–4. To make informed and safe decisions for patients negotiating this complex system, clinicians need the right information about the right patient in the right place at the right time 5.…”
Section: Introductionmentioning
confidence: 99%